LGBT Perspektif Fitrah, Hukum Syariah dan Tafsir al-Qur’an Depag R.I Surah al-A’raf Ayat 80-81 - Aulia, M. Ayatullah Firman (STAI Darul Kamal NW Kembang Kerang, 2024)
Abstract: There is no verse in the Quran that explicitly mentions LGBT (lesbian, gay, bisexual, and transgender) groups. The term LBGT is based solely on the analysis of scholars' approach and munasabah to the verse on the word fahisiyah or al-Fahasya. This research is a literature study using primary data from tafsir al-Quran, tafsir documents from the Ministry of Religious Affairs of the Republic of Indonesia, and secondary data from books and other articles related to the discussion of LGBT. This research is conducted using the Maudui data collection method. That is, setting the topic of discussion, searching and collecting verses of the Qur'an that have similar themes and arguments, and explaining the interpretation of verses related to the topic of sexual disorientation. After collecting all the data, the next step is to analyze the data using descriptive and contextual analysis. The main variable is the Qur'anic verse. Then, the text is explained, categorized, and interpreted objectively based on the Hadith and scholarly opinions on the subject under discussion. Therefore, from the above explanation, we can conclude that LGBT is a deviant act and is clearly prohibited in Islam, as stated in the interpretation book of the Indonesian Ministry of Religious Affairs. Keywords: LGBT, Tafsir Depag RI, Qs. al-A'raf Verse 80-81